PKM Kelompok Tani Tan Selo 1 dan Tan Selo 2 Desa Sukomaju Kecamatan Srono Kabupaten Banyuwangi Jawa Timur dalam Meningkatkan Nilai Ekonomis Pisang dan Strategi Pemasarannya - Nurmasari, Fitri; Padillah, Raup (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
Banyuwangi Regency is one of the agricultural centers in East Java province and Indonesia. Mostly,Banyuwangi people work as farmers due to the fertil soil and wide amount of agricultural land in Banyuwangi . Thelarge number of people who work as farmers initiating the formation of farmer groups. One of the farmer groups in theSrono sub-district of Banyuwangi is the